HERG1 gene expression as a specific tumor marker in colorectal tissues - Dolderer, Jürgen H.; Schuldes, Horst; Bockhorn, Hermann; Altmannsberger, Michael; Lambers, Christopher; Zabern, Detlef von; Jonas, Dietger; Schwegler, Herbert; Linke, Rüdiger; Schröder, Ulrich H. (European journal of surgical oncology, 2010)
Introduction - Colorectal carcinomas exhibit a frequent recurrence after curative surgery, which may partially be due to histopathologically inconspicuous minimal residual disease. Reliable markers for tumor cells in colorectal tissue are still missing. Therefore, in this study we compared the predictive value of the putative tumor markers carcinoembryonic antigen (CEA), cytokeratin-19 (CK19) and cytokeratin-20 (CK20) to that of a novel marker, the human ether-a-go-go-related gene (HERG1) K+ channel, a suggested regulator of tumor cell proliferation. - Materials and methods - Using RT-PCR we studied HERG, CEA, CK19 and CK20 expression in colorectal carcinomas and non-carcinoma controls. HERG1 immunhistochemistry was performed in a total of 66 specimens, in colorectal carcinoma (n = 23), in matched histopathologically negative samples (n = 23) taken near the excision site from the same tumor patients and in healthy control biopsies (n = 20). In order to verify the relevance of HERG1 for tumor proliferation we studied the effect of HERG1 inhibition in the Colo-205 colon cancer carcinoma cell line using the MTT-assay. - Results - HERG1 was expressed in all tumor samples regardless of their stage and in adenomas larger than 0.4 cm, but absent in small adenomas, sigmadiverticulitis specimen and healthy histopathologically negative samples, except for one which developed a tumor recurrence. In contrast, CEA, CK19 and CK20 were absent in some tumors. The selective HERG1 inhibitor E-4031 dose-dependently impaired tumor growth in the proliferation assays. - Discussion - Our data indicate that HERG1, but not CEA, CK19 or CK20, is a highly sensitive and reliable tumor biomarker that may constitute a novel molecular target for tumor treatment.
Available online 4 July 2009
Gesehen am 15.05.2023